Production Comparison of Three Genetic Strains of Freshwater Prawn, Macrobrachium rosenbergii, Raised Under Two Pond Management Technologies. Issue 5 (October 2014) - Tidwell, James H.; Odeyemi, Oluwapelumi O.; Coyle, Shawn D.; Schneider, Kyle J.; Bright, Leigh A.
Abstract Three genetic strains (Texas [cultured], Hawaii [cultured], and Myanmar [wild]) of freshwater prawn, Macrobrachium rosenbergii, were characterized and compared under two pond grow‐out management technologies using a 3 × 2 factorial design. Juvenile prawns (45 d nursed juveniles) from each strain were stocked at individual average weights of 0.4 ± 0.3 g (Texas), 0.3 ± 0.2 g (Hawaii), and 0.3 ± 0.2 g (Myanmar). The low input management technology prawns were stocked at 24, 700 /ha with no added substrate. The high input management technology prawns were stocked at 74, 100 /ha with the addition of artificial substrate. Each of the six treatment combinations were replicated in three, 0.04 ha earthen ponds (total of 18 ponds). Prawns were fed a sinking pellet (32% protein) once daily at a standardized rate. After 112 d, prawns were harvested, bulk weighed, and counted. Survival of Texas strain (95%) was significantly higher (P ≤ 0.05) than Myanmar strain (77–80%) under both management technologies with survival of Hawaii strain (86–91%) intermediate and not significantly different (P > 0.05) from other strains. Under both management technologies, average weight, total production, and marketable percentage (>20 g) was significantly better (P ≤ 0.05) in Texas and Hawaii strains in comparison to the Myanmar strain. These data appear to indicate that the cultured strains evaluated in this study demonstrate positive impacts of domestication and do not indicate inbreeding depression.